Can a single dose of human papillomavirus (HPV) vaccine prevent cervical cancer? Early findings from an Indian study. Issue 32 (6th August 2018) - Sankaranarayanan, Rengaswamy; Joshi, Smita; Muwonge, Richard; Esmy, Pulikottil Okkuru; Basu, Partha; Prabhu, Priya; Bhatla, Neerja; Nene, Bhagwan M.; Shaw, Janmesh; Poli, Usha Rani Reddy; Verma, Yogesh; Zomawia, Eric; et al.
Abstract: Background: Human papillomavirus (HPV) vaccination is a major strategy for preventing cervical and other ano-genital cancers. Worldwide HPV vaccination introduction and coverage will be facilitated if a single dose of vaccine is as effective as two or three doses or demonstrates significant protective effect compared to 'no vaccination'. Methods: In a multi-centre cluster randomized trial of two vs three doses of quadrivalent HPV vaccination (Gardasil™) in India, suspension of the vaccination due to events unrelated to the study led to per protocol and partial vaccination of unmarried 10–18 year old girls leading to four study groups, two by design and two by default. They were followed up for the primary outcomes of immunogenicity in terms of L1 genotype-specific binding antibody titres, neutralising antibody titres, and antibody avidity for the vaccine-targeted HPV types and HPV infections. Analysis was per actual number of vaccine doses received. This study is registered with ISRCTN, number ISRCTN98283094; and with ClinicalTrials.gov, number NCT00923702. Findings: Of the 17, 729 vaccinated girls, 4348 (25%) received three doses on days 1, 60, 180 or later, 4979 (28%) received two doses on days 1 and 180 or later, 3452 (19%) received two doses on days 1 and 60, and 4950 (28%) received one dose. One dose recipients demonstrated a robust and sustained immune response against HPV 16 and 18, albeit inferior to that of 3- or 2-doses and the antibody levels were stable over a 4 year period. The frequencies of cumulative incident and persistent HPV 16 and 18 infections up to 7 years of follow-up were similar and uniformly low in all the vaccinated study groups; the frequency of HPV 16 and 18 infections were significantly higher in unvaccinated age-matched control women than among vaccine recipients. The frequency of vaccine non-targeted HPV types was similar in the vaccinated groups but higher in the unvaccinated control women. Conclusion: Our results indicate that a single dose of quadrivalent HPV vaccine is immunogenic and provides lasting protection against HPV 16 and 18 infections similar to the three- and two-dose vaccine schedules, although the study suffer from some limitations. Data on long term protection beyond 7 years against HPV infection and cervical precancerous lesions are needed before policy guidelines regarding a single dose can be formulated and implemented. Significant and long-lasting protective effect of a single dose can be a strong argument to introduce one dose of the HPV vaccine in many low income countries where the current standard of care for cervical cancer prevention is 'no intervention'.